Study of an electrochemical behaviour of modified binary self-assembled monolayers for enhancing sensitivity of Hg(II) detection - Huyen, Dang Thanh; Loi, Vu Duc; Phong, Pham Hong (Vietnam Journal of Chemistry, 2016)
In the present study, an electrochemical behavior, the charge (Q) estimated from reductive desorption voltammograms, of the binary self-assembled monolayer (SAMs) prepared by immersing the primary 4-pyridineethanethiol (PET-SAM) into the solution of 2-aminoethanethiol (AET) was investigated for enhancing the sensitivity of Hg(II) detection. The optimized conditions was selected to be 20 minutes for immersion in the concentration of 0.1 mM AET solution to reach the maximum peak current (ipHg) obtained by differential pulse voltammetry for detection of Hg(II). Interestingly, the variation of Q by these factors was similar with that of ipHg, indicating the role of the introduction of the second component, AET, in kinetic formation of the binary SAMs for enhancing sensitivity of Hg(II) detection at ultra trace level. Keywords. Self-assembled monolayer, binary SAMs, 4-pyridineethanethiol, 2-aminoethanethiol.